The Effect of Religious Culture and Time Management on The Observance of School Rules at State Junior High School 9 Prabumulih - Marlina, Marlina; Hartatiana, Hartatiana; Zulhijra, Zulhijra (Journal of Educational Sciences, 2025)
This study aims to analyze the effect of religious culture and time management on obedience to the implementation of school rules, both partially and simultaneously, at SMP Negeri 9 Prabumulih. Obedience to discipline is an important indicator in creating a conducive educational environment, so strong supporting factors are needed, such as an internalized religious culture and good time management skills. This research uses a quantitative approach with descriptive analysis method. The population in this study were all teachers and education personnel totaling 52 people, while a sample of 20 people was taken through random sampling technique. Data collection techniques include observation, questionnaires, and documentation, which are then analyzed using the t test for partial influence and the F test for simultaneous influence. The results showed that religious culture and time management had a significant effect partially on obedience to the implementation of discipline. Simultaneously, the two variables contributed 90.9%, while 9.1% was influenced by other factors outside the study. The findings suggest that the cultivation of religious values and effective time management need to be improved as part of the strategy of character building and discipline in the school environment.